2019
DOI: 10.1002/bit.26880
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing modes of action and interaction for multicomponent osmolyte solutions on Jurkat cells

Abstract: This study examined the post‐thaw recovery of Jurkat cells cryopreserved in three combinations of five osmolytes including trehalose, sucrose, glycerol, mannitol, and creatine. Cellular response was characterized using low‐temperature Raman spectroscopy, and variation of post‐thaw recovery was analyzed using statistical modeling. Combinations of osmolytes displayed distinct trends of post‐thaw recovery, and a nonlinear relationship between compositions and post‐thaw recovery was observed, suggesting interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The combination of previous studies (Pollock et al, 2016;Pi et al, 2019b) and new findings from this investigation provides insights into how the DMSO-free CPAs act to protect the hiPSCs from freezing damage. Mechanisms of cryoprotection for DMSO-free CPAs differ from that of DMSO, which is an organic solvent.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The combination of previous studies (Pollock et al, 2016;Pi et al, 2019b) and new findings from this investigation provides insights into how the DMSO-free CPAs act to protect the hiPSCs from freezing damage. Mechanisms of cryoprotection for DMSO-free CPAs differ from that of DMSO, which is an organic solvent.…”
Section: Discussionmentioning
confidence: 71%
“…Both DOE and Taguchi methods assume that the topology of the parameter space that is being studied is unimodal and that there are no interactions between parameters. Both of these assumptions are not true, as this study has demonstrated that the topology is not unimodal, and our statistical model (Pi et al, 2019b) has shown that that there are synergistic effects between the CPA molecules tested, making these alternative approaches unsuitable. Emergent population staying constant for two generations was defined as the criterion of convergence for the DE algorithm.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These might account for loss of functional cells in cryopreserved T-cell product for immunotherapy. In comparison, DMSO-free freezing media composed of sugars, sugar alcohols and amino acids have been demonstrated to successfully preserve Jurkat cells as a CD3 + CD4 + T-lymphocyte model with high postthaw viability [8,64] and can potentially be used to cryopreserve other types of T cells. Similar to T cells, although NK cells cryopreserved in DMSO have shown significant functional loss in terms of their cytotoxicity [60], a DMSO-free freezing medium composed of poly-l-lysine, dextran and ectoine has demonstrated improved post-thaw cytotoxicity in cryopreserved NK cells [65].…”
Section: Emerging Approachesmentioning
confidence: 98%
“…The MCO solution was prepared by adding trehalose, glycerol, and isoleucine directly to Normosol‐R and mixed using a vortex mixer until a clear liquid was formed. The concentration of each component of the TGI MCO has been published previously 14 . A 10% vol/vol.…”
Section: Methodsmentioning
confidence: 99%